ETIKA BISNIS SEBAGAI ACUAN MENINGKATKAN KEPUASAN KONSUMEN: STUDI PADA BISNIS ONLINE - Ari Sumaryati, Sri (Universitas Pawyatan Daha, 2022)
In the digital era of business that is growing rapidly, almost all products are offered through online media, various online business applications such as Lazada, Shopee, Tokopedia, Bukalapak and others are easily accessible that offer each product with various advantages and convenience in transacting and various payment system options, starting with bank transfers, joint accounts, and cod (cost order delivery) which are currently increasingly popular with the public. To ensure a smooth business that gives satisfaction to consumers as desired and on the other hand the seller gets a positive response, business ethics is needed to encourage moral awareness and provide boundaries for users or business people to run good business and not do monkey business or dirty business.